The basic structure of the Zaiwa noun phrase - Wannemacher, Mark (2024)
This paper provides a basic description of major grammatical features of the Zaiwa noun phrase. It includes a review of Zaiwa phonology, a discussion of word classes and consituent order typology, and a description of the noun phrase including noun types, nominal modifiers, conjunctions and aspects of discourse grammar related to the noun phrase.